Java cryptography - Knudsen, Jonathan (Java series (O'Reilly & Associates), 1998)
Cryptography, the science of secret writing, is the biggest, baddest security tool in the application programmer's arsenal. Cryptography provides three services that are crucial in secure programming. These include a cryptographic cipher that protects the secrecy of your data; cryptographic certificates, which prove identity (authentication); and digital signatures, which ensure your data has not been damaged or tampered with. This book covers cryptographic programming in Java. Java 1.1 and Java 1.2 provide extensive support for cryptography with an elegant architecture, the Java Cryptography Architecture (JCA). Another set of classes, the Java Cryptography Extension (JCE), provides additional cryptographic functionality. This book covers the JCA and the JCE from top to bottom, describing the use of the cryptographic classes as well as their innards. The book is designed for moderately experienced Java programmers who want to learn how to build cryptography into their applications. No prior knowledge of cryptography is assumed. The book is peppered with useful examples, ranging from simple demonstrations in the first chapter to full-blown applications in later chapters. Topics include: The Java Cryptography Architecture (JCA) The Java Cryptography Extension (JCE) Cryptographic providers The Sun key management tools Message digests, digital signatures, and certificates (X509v3) Block and stream ciphers Implementations of the ElGamal signature and cipher algorithms A network talk application that encrypts all data sent over the network An email application that encrypts its messagesCovers JDK 1.2 and JCE 1.2.